The use of Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography Mass Spectroscopy (GCMS) for Halal Authentication in Imported Chocolate with Various Variants - Suparman, Suparman (Journal of Food and Pharmaceutical Sciences, 2015)
The analysis using FTIR and GCMS spectrophotometry for halal authentication on several variants of imported chocolate products circulating on the market has been performed. FTIR spectra analysis result of lard and chocolate in the wave number region of 4000-650 cm-1 shows a typical lard-specific difference at wavenumber region 3006.8 cm-1; 1118.84 cm-1; 1097.42 cm-1. Analysis of PCA and PLS calibration models in the fingerprint region 999.053 - 1190.638cm-1 can be used for lard identification in chocolate fat. The relationship between the actual value and the predicted value of lard in chocolate yields the equation Y= 1,000x-0,0378, (R2 0,997 and RMSEC 1,563) with a minimum limit of detection at a concentration of 4%. Based lard chromatogram, it shows the peak appeared at a retention time of 38,8 minutes. After being compared with library WILLEY7, it shows eikosadienoat 11.14 acidic compounds. Eikosadienoat 11.14 acid is a marker of the presence of lard appearing with a mixture of lard concentration at â‰¥ 10%. FTIR spectra and analysis results using PCA and PLS on samples of 6 imported chocolate variants show a lard content which is marked by the appearance of eikosadienoat 11.14 acid at a retention time of 38,8 minutes in the chromatogram. PLS quantitative analysis shows lard content in the sample is 43.6%; 73.5%; 61.7%; 63.0%; 37.0%; and 30.4%.Keywords: Â FTIR, GCMS, Eikosadienoat, Chocolate